PANJANG TUNGKAI BERHUBUNGAN DENGAN KECEPATAN BERLARI SPRINT 60 METER SISWA KELAS V - VI di SDN KEBONAGUNG 01 - Bani Adam, Farid; Nilawati, Ika; Aristiyanto, Aristiyanto; Amin, Nur (Sports Collaboration Journal, 2023)
Short distance sprinting is a race where athletes use full speed over distances of 60 meters, 80 meters, 100 meters, 200 meters and 400 meters. A runner must know the basics of sprinting techniques so that the runner can get maximum results. The aim of this research was to determine the relationship between leg length and 60 meter sprint running speed for students in classes V-VI at SDN Kebonagung 01. This research used a survey method with a total sampling technique of 20 students. The data collected for the leg length variable used a meter, sprint speed used a stopwatch and a meter. Data analysis used the Spearman's Test correlation test. The results of this research included the 60 meter sprint for class V-VI students at SDN Kebonagung 01, which resulted in the speed of 14 students in the men's category (70%), the speed of the women's category in 6 students (30%). Based on the correlation test, the results showed that there was a relationship between leg length and running with a p-value of 0.02. The conclusion of this research is that there is a relationship between leg length and running in students at SDN class V-VI Kebonagung 01. ABSTRAK Lari sprint jarak pendek adalah suatu perlombaan dengan atlet yang menggunakan kecepataan penuh dengan jarak 60 meter, 80 meter, 100 meter, 200 meter, dan 400 meter. Seorang pelari wajib pengetahui dasar-dasar teknik lari sprint supaya pelari tersebut mendepatkan hasil yang maksimal. Tujuan dalam penelitian ini adalah untuk mengatahui hubungan panjang tungkai dengan kecepatan lari sprint 60 meter siswa kelas V-VI SDN Kebonagung 01. Penelitian ini menggunakan metode survei dengan teknik total sampling pada 20 siswa. Pengambilan data yang digunakan pada variabel panjang tungkai menggunakan meteran, kecepatan lari sprint menggunakan stopwatch dan meteran. Analisis data menggunakan uji korelasi Spearman’s Test. Haisl Penelitian ini antara lain lari sprint 60 meter siswa kelas V–VI SDN Kebonagung 01 mendapatkan hasil kecepatan kategori Putra 14 siswa (70%), kecepatan kategori Putri 6 siswi (30%). Berdasarkan uji korelasi didapatkan hasil bahwa terdapat hubungan antara panjang tungkai dengang berlari dengan nilai p-value 0.02. Kesimpulan dari penelitian ini adalah terdapat hubungan antara panjng tungkai dan berlari siswa SDN kelas V-VI Kebonagung 01